Effectiveness of activated carbon and Fenton reagent in the treatment of wastewater from green olive processing - Miranda Gutierrez, Junior Soviet (2024)
The olive industry (OI) generates large quantities of contaminated wastewater, especially during the alkaline treatment of green olives, posing an environmental problem due to the high levels of organic matter, phenolic compounds, and salts present in these effluents. The aim of this study was to evaluate the effectiveness of two treatments, adsorption with activated carbon and Fenton reagent, to reduce biochemical oxygen demand (BOD5) and chemical oxygen demand (COD) in OI wastewater. Samples were collected from three affected zones in Tacna, Peru, and both treatments were applied using different reagent concentrations. The analysis included measuring BOD5 and COD before and after the treatments, followed by statistical tests to validate the results. The findings showed that although both methods achieved significant reductions in BOD5 and COD, Fenton’s reagent was more efficient in reducing COD in all zones, while activated carbon was more effective in reducing BOD5 in areas with high organic loads. In conclusion, the choice of treatment will depend on the specific conditions of the wastewater, with Fenton’s reagent being more suitable for areas with moderate organic contamination.